Is it worthwhile to conduct a randomized controlled trial of glaucoma screening in the United Kingdom?. (January 2014) - Burr, Jennifer; Hernández, Rodolfo; Ramsay, Craig; Prior, Maria; Campbell, Susan; Azuara-Blanco, Augusto; Campbell, Marion; Francis, Jill; Vale, Luke
Objectives: To assess the value of conducting a glaucoma screening randomized controlled trial in the UK. Methods: Decision model based economic evaluation and value of information analysis. Model derived from a previous health technology assessment. Model updated in terms of structure and parameter estimates with data from surveys, interviews with members of the public and health care providers and routine sources. Results: On average, across a range of ages of initiating screening (40–60 years), glaucoma prevalence (1–5%), screening uptake (30–100%), and the performance of current case finding, screening was not cost-effective at a £30, 000 threshold per quality adjusted life year (QALY) from the perspective of the National Health Service (NHS). The societal value of removing all uncertainty around glaucoma screening is £107 million at a threshold of £20, 000 per QALY. For informing policy decisions on glaucoma screening, reducing uncertainty surrounding the NHS and personal social care cost of sight impairment (£74 million) was of most value, followed by reducing uncertainty in test performance (£14 million) and uptake of either screening or current eye care (£8 million each). Conclusions: A glaucoma screening trial in the UK is unlikely to be the best use of research resources. Further research to quantify the costs of sight impairment falling on the NHS and personal social services is a priority. Further development of glaucoma tests and research into strategies to promote the uptake of screening or current eye care such as through the use of a behavioural intervention would be worthwhile.